Protective Effect of Benfotiamine against Doxorubicin-Induced Cardiotoxicity in Rabbits. - Munaf H. Abdulrazzaq (College of Pharmacy University of Baghdad, 2017)
The protective effect of benfotiamine against doxorubicin-induced cardiotoxicity was evaluated in rabbits. Pretreatment of rabbits with 70mg/kg benfotiamine orally 7 days before induction of cardiotoxicity with I.V 15mg/kg doxorubicin. injection resulted in significant reduction of the activities of lactate dehydrogenase and creatine phosphokinase enzyme in the serum compared to doxorubicin treated animals; benfotiamine also improves the histological changes produced by doxorubicin in the cardiac muscle compared to control. In conclusion, benfotiamine when used concomitantly with doxorubicin protects the myocardium against the cardiotoxicity induced by this cytotoxic drug.